KEADILAN PROPORSIONAL DALAM PEMBAGIAN WARIS ANAK ANGKAT - Ramadhita, Ramadhita (Fakultas Syariah, 2012)
The existence of a religion in the modern era, is determined by its velocity to respond and resolve the problems of life creatively, by means of ijtihad, with a wide range of its methodology. A progressive steps have been carried out by Indonesian’s scholars by giving rights to the relics of a foster child by testament wajibah, regulated in article 209 compilation of Islamic law. Though it is never cached prearranged classical fiqh. Thus, even though in its development of article 209 hasn’t been able to reflect justice. Therefore, the part that was accepted by the adopted child may be smaller than the other heirs, regardless of contributions or services that have been given a foster child to adoptive parents Eksistensi suatu agama di era modern, ditentukan bagaimana merespon dan menyelesaikan problem kehidupan secara kreatif dengan cara ijtihad, dengan berbagai macam metodologinya. Langkah progresif telah dilakukan oleh ulama Indonesia dengan memberikan hak dari harta peninggalan kepada anak angkat melalui wasiat wajibah, yang diatur dalam Pasal 209 Kompilasi Hukum Islam. Padahal hal ini tidak pernah diatur sebelumnya di dalam khazanah fiqh klasik. Meskipun dimikian, dalam perkembangannya Pasal 209 belum mampu mencerminkan keadilan. Sebab, bagian yang diterima oleh anak angkat bisa jadi lebih kecil dari bagian ahli waris lain, tanpa mempertimbangkan kontribusi atau jasa yang telah diberikan anak angkat kepada orang tua angkatnya.